Aliocis, a replacement name for the preoccupied ciid genus Anoplocis Kawanabe, 1996 (Coleoptera: Tenebrionoidea: Ciidae) - Sandoval-Gómez, Vivian Eliana; Lopes-Andrade, Cristiano (Zootaxa, 2015)
The Ciidae genus Anoplocis was established by Makoto Kawanabe (1996) based on the type species Ennearthron poriae Nakane & Nobuki, 1955 from Japan. Additionally, he described the Japanese species Anoplocis ryukyuensis Kawanabe, 1996. However, the name Anoplocis was previously proposed by Arthur M. Lea (1913) for a genus of true weevils (Coleoptera: Curculionidae), with its type species Anoplocis ferrugineus Lea, 1913 from Australia. In consequence, the genus Anoplocis Kawanabe, 1996 is a junior homonym of the genus Anoplocis Lea, 1913. According to Article 60 of the International Code of Zoological Nomenclature, we propose the replacement name Aliocis nom. nov. for Anoplocis Kawanabe, 1996. New combinations are here proposed for the two species included in this genus: Aliocis poriae (Nakane & Nobuki, 1955) comb. nov. and Aliocis ryukyuensis (Kawanabe, 1996) comb. nov.